Method for Isolation of Myxozoan Proliferative Stages from Fish at High Yield and Purity: An Essential Prerequisite for In Vitro, In Vivo and Genomics-Based Research Developments - Ana Born-Torrijos; Anush Kosakyan; Sneha Patra; Joana Pimentel-Santos; Brian Panicucci; Justin Tze Ho Chan; Tomáš Korytář; Astrid S. Holzer (Cells, 2022)
Myxozoans are a diverse group of microscopic cnidarian parasites and some representatives are associated with important diseases in fish, in both marine and freshwater aquaculture systems. Research on myxozoans has been largely hampered by the inability to isolate myxozoan parasites from their host tissues. In this study, we developed and optimized a method to isolate the myxozoan proliferative stages of different size and cellularity from fish blood, using DEAE-cellulose ion exchange chromatography. We optimized several parameters and obtained 99–100% parasite purity, as well as high survival and infectivity. Using polyclonal pan-carp blood cell-specific antibodies, we further developed a rapid cytometric assay for quantification of the proliferative stages, not only in highly concentrated DEAE-C isolates but also in dilute conditions in full blood. Early developmental stages of myxozoans are key to parasite proliferation, establishment, and pathology in their hosts. The isolation of these stages not only opens new possibilities for in vivo and in vitro studies, but also for obtaining purified DNA and protein extracts for downstream analyses. Hence, we provide a long-desired tool that will advance the functional research into the mechanisms of host exploitation and immune stimulation/evasion in this group, which could contribute greatly to the development of therapeutic strategies against myxozoans.